Pengaruh Antrean Dan Tundaan Kendaraan Terhadap Penggunaan Bahan Bakar Pengoperasian Palang Pintu Kereta - Fadholi, Muhammad; Theresia, Theresia (Jurnal Etnik: Ekonomi-Teknik, 2023)
Transportation is the movement of people or goods using tools or vehicles from the place of origin to the destination. A level crossing is a meeting or intersection of a road with a railroad. Closing the doorstop causes the flow of traffic on the road to stop until the train passes which results in queues and vehicle delays which have an impact on fuel consumtion. This study aims to determine queues, vehicle delays and their effect on fuel use.This study uses a quantitative method with data obtained from the field, namely closing duration data, vehicle queue duration data, queue length data and vehicle volume data. data were obtained from the field for 7 days and the 3 busiest days were selected, namely Monday, Wednesday and Saturday, then analyzed using multiple linear regression.Based on the analysis, the average queue length of vehicles at level crossings on Jl. Hayam Wuruk on Monday is 71.368 m, Wednesday is 68.263 meters, and Saturday is 79.947 m. Data on average vehicle delays at level crossings on Jl. Hayam Wuruk on Monday was 281 seconds, Wednesday was 211 meters, and Saturday was 238.453 seconds. The ATIS – India method of the fuel use equation model is Y = - 0.717 + 0.005 X1 + 0.003 X2.